Participation of the renin-angiotensin system in experimental renovascular hypertension (Revista Española de Fisiología, 1983)
Hypertension was induced in Wistar rat by means of a clip in the left renal artery.After two weeks (acute stage) and sixteen weeks (chronic stage) the animals had a significant increase in arterial pressure (AP) and plasma renin activity (PRA).At both stages, nephrectomy or revascularization of the ischemic kidney returned AP and PRA to the normal level, both in the short term (1 day) and long term (60 days).